The relevance of coagulation in cardiovascular disease: what do the biomarkers tell us? - Lowe, Gordon; Rumley, Ann (Thrombosis and Haemostasis, 2014)
Several haemostatic factors have been associated with incident arterial cardiovascular disease in prospective studies and meta-analyses. Plasma fibrinogen shows a strong and consistent association with risk; however, this may reflect its inflammatory marker status, and causality remains to be proven. The common haemostatic gene polymorphisms for factor II, factor V and the von Willebrand factor: Factor VIII (non-O blood group) show significant associations with coronary heart disease (CHD) risk, consistent with potential causality. Increased D-dimer and t-PA antigen levels are associated with CHD risk, suggesting roles for coagulation activation and endothelial disturbance. There is little evidence for associations with CVD with other haemostatic factors.
Keywords: Arterial thrombosis; epidemiological studies; coagulation factors